Wordwall Puzzle Educational Game Application Integrated with Ngada Local Culture “Ngadhu_Bhaga” to Improve Cognitive Abilities in Early Childhood - Fono, Yasinta Maria; Nafsia, Andi; Owa Mere, Veronika (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
This research was motivated by the lack of contextual learning media based on local culture, which makes learning less relevant to children's environment and less optimal in stimulating their cognitive abilities. This research is a type of Research and Development (R&D) study that aims to develop an educational game application, Wordwall Puzzle integrated with Ngada local culture, titled “Ngadhu-Bhaga,” to enhance the cognitive abilities of young children. The development of the application follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects involved two teachers and 20 early childhood students. Data collection techniques included observation, questionnaires, and interviews. The research instruments consisted of validation sheets from three experts (content expert, application design expert, and language expert), a cognitive development questionnaire for children, and an application trial instrument. The collected data were analyzed using both qualitative and quantitative descriptive approaches. Qualitative analysis was used to evaluate expert feedback for improving the quality of the product, while quantitative analysis was conducted on the questionnaire data using the Likert scale to assess the practicality and effectiveness of the product as well as children's cognitive development. The validation results showed that the application received excellent ratings from the content expert (4.60), application design expert (4.35), and language expert (4.48). Trials with teachers yielded an average score of 4.49 and with students 4.54, both falling into the “very good” category. Based on these results, it can be concluded that the application is feasible to be used as an interactive learning medium that also supports the preservation of local culture.